Sustainable logistics and supply chain management : principles and practices for sustainable operations and management - Grant, David B.; Trautrims, Alexander; Wong, Chee Yew (London : KoganPage, 2023)
"Sustainable Logistics and Supply Chain Management is an essential textbook for undergraduate and postgraduate students for understanding sustainability as it pertains to logistics operations. This book covers the direct environmental impacts of logistics and supply chain processes, including emissions and waste, as well as how wider changes such as globalization need to be given similar considerations. Presenting different pathways to guide readers, case studies and supported by extensive research, this book provides all the support needed to understand and implement a sustainable approach"--
Previous edition: 2017.
Includes bibliographical references and index.
Keywords: Business logistics; Production management; Business logistics; Production management